(untitled) (American Journal of Islam and Society, 2011)
Emon’s Islamic Natural Law Theories, is an excellent source of research for specialists in Islamic jurisprudence. It is not for the general public. Emon divides his work into five chapters: Introduction, Hard Natural Law, The Critique of Hard Natural Law, Soft Natural Law, and Conclusion. Both his style and his usage of words are fascinating. His understanding of the premodern works on Islamic jurisprudence (usul al-fiqh) reflects his indepth research and comprehension of classical works. His rendering of jurisprudential terms (alfaz usuliyyah) into English language also marks his great familiarity with Islamic sources. This work is an excellent addition to the literature on Islamic law. Emon’s work focuses on the ontological authority of reason in the Shari‘ah. He investigates the use of reason in establishing a rule of law alongside the source texts. He explicates the meanings of natural law as understood by premodern jurists and explains to what extent, in the absence of source texts, can good and bad (husn and qubh) assume sufficient normative authority, which will result in Shari‘ah obligation. Emon affirms that the use of reason in Shari‘ah has been debated extensively by Muslim jurists. While many scholars rejected the authority of reason in legislation, others endorsed it. However, in practice, all scholars resort to it in one form or another. From chapter one to the end, Emon successfully explains with lucidity the concept of good and bad. He analyzes this concept from the perspectives of major Muslim scholars from different schools of Islamic jurisprudence. He selects leading scholars from each school ‒ like Qadi Abdul Jabbar, Abu Husayn al-Basri, Abu Bakr al Jassas, al-Ghazali, al-Qarafi, al-Shatibi, Ibn Hazm al-Zahiri, and others ...